The Needs Analysis in the Development of Level of Inquiry with Project Assignments Model to Promote the Creativity of Prospective Physics Teachers - Wahyudi; Setiawan, Agus; Suhandi, Andi; Samsudin, Achmad (LPPM Undiksha, 2023)
This Inquiry and project-based learning models play an essential role in developing 21st-century skills, especially the development of creativity for prospective physics teacher students (PPTs). Developing and integrating these two models requires a needs analysis as the first step of development. Therefore, this study aims to conduct a needs analysis for developing a level inquiry model with project assignments. This research uses a descriptive study. The needs assessment study method with a convergent analysis approach is used in this study. Data sources in this study include curriculum documents in the form of Semester Lesson Plan (SLP) and practicum guidance modules for introductory physics courses. Perception data was also collected from respondents from 33 PPTs and lecturers of introductory physics courses. The data collection techniques used were documentation, questionnaires and interviews. The results of the study concluded that the curriculum for introductory physics lectures contained scientific and creative skill competencies for PPTs. However, lecturers still dominate learning, and physics practicum activities have not yet led to an appropriate inquiry learning process and project learning is rarely implemented. The creativity of PPTs has not been optimized in learning physics. Lecturers and students responded that developing the Level of Inquiry with Project Assignments Model (LoI-PA) is very important to increase the creativity of PPTs. The LoI-PA hypothetical model is presented in the discussion of this study. However, further research is still needed to develop valid learning steps and integrate information technology into the learning model steps.